Mental health presentations to the paediatric emergency department: A retrospective study. (6th January 2021) - Say, Daniela F; Carison, Anna; Hill, Ashley; Hiscock, Harriet; Babl, Franz E; O'Donnell, Sinead M
Abstract : Aim: To describe a cohort of patients aged 7–17 years presenting with mental health (MH) problems to an Australian tertiary paediatric emergency department (ED), in order to identify: (i) predictors of admission; and (ii) prolonged length of stay (LOS); (iii) reasons for ED presentation based on diagnosis and (iv) differences between major diagnostic groups. Methods: Data for all presentations from 1 January 2018 to 31 December 2018 were extracted and analysed from the hospital's electronic medical record system. MH presentations were identified though rule‐based coding and manual file review. Results: In this 12‐month period, 1071 children had 1690 emergency MH presentations constituting 6.7% of all ED presentations for children aged 7–17 years. Collectively, the leading cause for presentations was suicidal ideation, self‐harm or drug overdose (55%). Compared to discharged patients, admitted patients were more likely to be female (odds ratio (OR) 1.82, confidence interval (CI) 1.41–2.35), aged over 14–years (OR 2.50, CI 1.98–3.15), triaged with high acuity (OR 2.70, CI 2.00–3.65) and arrive by ambulance or police (OR 1.31, CI 1.04–1.64). The highest risk diagnosis associated with admission was eating disorders (OR 9.19, CI 5.48–15.40). Patients with a prolonged LOS (>8 h) were more likely to need admission (OR 5.38, CI 3.81–7.61) and be diagnosed with drug overdose (OR 2.39, CI 1.51–3.80) or acute behavioural disturbance (OR 1.61, CI 1.09–2.39). Conclusion: Mental health presentations constitute a large proportion of ED presentations. Suicidal behaviour and self‐harm account for half of them. We have identified patients at increased risk of admission and prolonged ED LOS.